2011
DOI: 10.1007/s10571-011-9713-2
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective Effects of 2-Cyclopropylimino-3-Methyl-1,3-Thiazoline Hydrochloride Against Oxidative Stress

Abstract: Oxidative stress, glutamate excitotoxicity, and inflammation are the important pathological mechanisms in neurodegenerative diseases. Recently, we reported that 2-cyclopropylimino-3-methyl-1,3-thiazoline hydrochloride protects rat glial cells against glutamate-induced excitotoxicity. In this study, we report the effects of 2-cyclopropylimino-3-methyl-1,3-thiazoline hydrochloride on primary cultured cortical astrocytes after exposure to hydrogen peroxide (H₂O₂). Pretreatment of cells with 2-cyclopropylimino-3-m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 37 publications
1
4
0
Order By: Relevance
“…These results suggest that 2-cyclopropylimino-3-methyl-1,3-thiazoline hydrochloride protected the brain against ischemia injury through regulation of the oxidation–reduction system, specifically by increasing antioxidant capacity. The antioxidant effects of 2-cyclopropylimino-3-methyl-1,3-thiazoline hydrochloride in vivo is consistent with the antioxidant and free-radical-scavenging properties of this compound in vitro (16).…”
Section: Resultssupporting
confidence: 74%
See 3 more Smart Citations
“…These results suggest that 2-cyclopropylimino-3-methyl-1,3-thiazoline hydrochloride protected the brain against ischemia injury through regulation of the oxidation–reduction system, specifically by increasing antioxidant capacity. The antioxidant effects of 2-cyclopropylimino-3-methyl-1,3-thiazoline hydrochloride in vivo is consistent with the antioxidant and free-radical-scavenging properties of this compound in vitro (16).…”
Section: Resultssupporting
confidence: 74%
“…Therefore, antioxidative agents may offer an effective therapeutic strategy against ischemic damage. Previous studies from our laboratory have demonstrated the ability of 2-cyclopropylimino-3-methyl-1,3-thiazoline hydrochloride against oxidative stress in primary cultured cortical astrocytes (16). 2-Cyclopropylimino-3-methyl-1,3-thiazoline hydrochloride also protected against damage from glutamate, an excitotoxic neurotransmitter (14).…”
Section: Resultsmentioning
confidence: 82%
See 2 more Smart Citations
“…5) significantly reduced A␤ 25-35 -induced primary cortical neuronal cell neurotoxicity [901]. The compound also suppressed glutamate-induced excitotoxicity [902], produced anti-inflammatory effects [903] and showed neuroprotective effects against oxidative stress [904].…”
Section: Khg-26377mentioning
confidence: 94%